2005
DOI: 10.1007/s00415-005-0840-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with drug–induced visual hallucinations in Parkinson's disease

Abstract: Our findings indicate that apart from well established risk factors such as cognitive impairment and disease duration, disease severity is also important for the development of visual hallucinations in PD. Furthermore, the presence of bradykinesia and instability, the absence of tremor and the severity of rigidity and bradykinesia (limb and axial) may act as cofactors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…VH were thus initially considered to be a druginduced phenomenon,and were classified as "dopaminomimetic psychosis" or "levodopa psychosis" [3,4,[6][7][8][9][10][11], despite earlier reports showing that VH may occur as a consequence of anticholinergic treatments [12].…”
Section: Introductionmentioning
confidence: 99%
“…VH were thus initially considered to be a druginduced phenomenon,and were classified as "dopaminomimetic psychosis" or "levodopa psychosis" [3,4,[6][7][8][9][10][11], despite earlier reports showing that VH may occur as a consequence of anticholinergic treatments [12].…”
Section: Introductionmentioning
confidence: 99%
“…Psychosis is consistently more common in PD patients with dementia, 7,9,11,[19][20][21] and cognitive impairment is a risk factor for later developing hallucinations. 9,22,23 Based on this, many studies have evaluated whether certain cognitive domains are preferentially impaired in PD patients with visual hallucinations.…”
Section: Cognitive and Visual Impairmentmentioning
confidence: 99%
“…7,11,12,15 Studies have also found that greater disease severity, as measured by the Activities of Daily Living subscale of the Unified Parkinson Disease Rating Scale (UPDRS Part II), is an independent risk factor for hallucinations in PD. 8,10,12,13 Papapetropoulos et al found that the total UPDRS score was an independent predictor of visual hallucinations in PD.…”
Section: Age Duration Of Disease and Disease Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Neurodegenerative disease, psychotropic medications, and psychological factors may all manifest with or exacerbate symptoms of visual dysfunction. [5][6][7][8][9][10][11][12][13][14] Such multifactorial visual complaints are difficult to diagnose, and may be best approached by a multidisciplinary team. 3 The Visual Perception Clinic in the Newcastle Eye Centre provides such a multidisciplinary service.…”
Section: Introductionmentioning
confidence: 99%